Combined transplantation of the heart and liver. - Shaw, B W (1985)
The technique of combined transplantation of the heart and liver is described and illustrated, emphasizing modifications that were used in a successful case. Two other unsuccessful attempts are reported, and the importance of relative size of donor and recipient is discussed. There may be an immunological advantage to transplanting two organs in combination from the same donor.